Pemanfaatan Media Sosial Twitter oleh Ridwan Kamil dan Ganjar Pranowo Telah Sesuai dengan Fungsi Utama Media Massa - Harrera, Andrea Eka Premasadha (Jurnal The Messenger, 2016)
The development of social media makes a lot of people should follow it. We are required to be able to use social media as a medium that can simplify our lives, as we can find a lot of  information or news through the media. On the other hand, social media can also facilitate the work  of  someone.  In  this   research,  the  researcher   want  to  see  that  social   media  twitter belonging to Ridwan Kamil and Ganjar Pranowo which they use as a medium to get closer to  the citizens, in accordance with the essential function of the mass media. This research using qualitative  research  method  with  observation  the  timeline  twitter of  @ridwankamil  and  @ganjarpranowo.   Then,   from  the  observation,   It  is indicate  that  the  twitter  account  has complied with all the essential functions of a mass media.